Relationship between anxiety and autonomic heart modulation - Pinheiro, Giovanni Vieira; Martiniano, Eli Carlos; Alcântara, Guilherme Correia; Silva, José Ramon Alcântara da; Silva, Maria do Socorro da; Monteiro, Larissa Raylane Lucas; Mangueira, Luana Bezerra; Moraes, Yasmim Mota de; Valenti, Vitor Engrácia; Santana, Milana Drumond Ramos (ABCS Health Sciences, 2018)
The anxiety is characterized by the sensation of tension, nervousness, apprehension and worry that can alter the modulation of autonomic nervous system on the electrical conduction linked to the heart, determining the intensity in the heart beats modifying the heart rate variability, which is an important indicator of conditions normal and pathological. Thus, the study objective is to analyze the relationship between anxiety and the process of autonomic cardiac regulation. This study is an integrative review developed through searches in the databases of Lilacs, Medline and SciELO, with the descriptors in health sciences and boolean operator: anxiety AND heart rate and anxiety AND autonomic nervous system. The search was performed during the month of September of 2017, being included articles available in full; in Portuguese and English and; published in the last 6 years. Was excluded articles that were not original, theses, dissertations and monographs. Was obtained a total of 10 articles, in which it was observed that anxiety alters the autonomic response, so when the body is in tension, increases your heart rate, the predominance of the sympathetic system and in the relaxation occurs the domain of the parasympathetic. Thus, individuals with anxiety present lower variation in heart rate and have a lower capacity for social interaction. With this, it is evident a low adaptation of the autonomic nervous system in cases of anxiety, being that the variability of the heart rate is reduced; condition that can be classified as pathological.